2011
DOI: 10.4061/2011/689290
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Clinical Use of Therapeutic Hypothermia for Ischemic Stroke: Opportunities and Limitations

Abstract: Stroke remains a disease with a serious impact on quality of life but few effective treatments exist. There is an urgent need to develop and/or improve neuroprotective strategies to combat this. Many drugs proven to be neuroprotective in experimental models fail to improve patient outcome in a clinical setting. An emerging treatment, therapeutic hypothermia (TH), is a promising neuroprotective therapy in stroke management. Several studies with TH in experimental models and small clinical trials have shown bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…At present, most clinical therapeutic hypothermia (TH) protocols involve methods of forced cooling such as with cold blankets and ice baths or intravenous methods of cooling (25). Although TH seems to have significant promise in stroke therapy, current protocols are accompanied by many adverse complications, which reduce effectiveness and preclude broad application (21,50).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, most clinical therapeutic hypothermia (TH) protocols involve methods of forced cooling such as with cold blankets and ice baths or intravenous methods of cooling (25). Although TH seems to have significant promise in stroke therapy, current protocols are accompanied by many adverse complications, which reduce effectiveness and preclude broad application (21,50).…”
mentioning
confidence: 99%
“…Thrombolysis is the only approved method for stroke therapy (41), but it can be applied to less than 10% of the patients due to the stringent treatment criteria (26) and in some cases may even produce further reperfusion injury (2). Mild hypothermia (32-34°C) has been demonstrated to reduce stroke injury and improve neurofunctional recovery in animal studies and has shown promise in small-scale clinical trials (20,25,37,49,50). At present, most clinical therapeutic hypothermia (TH) protocols involve methods of forced cooling such as with cold blankets and ice baths or intravenous methods of cooling (25).…”
mentioning
confidence: 99%
“…Despite this significant promise in animal models, large-scale controlled clinical trials have yet to be performed to evaluate the effectiveness of hypothermia for treatment of stroke in humans. Significant impediments to these trials may include unfavorable balance between potential benefit and the difficulty in implementation, clinical complications and the high cost currently associated with traditional cooling protocols (6, 26). …”
Section: Discussionmentioning
confidence: 99%
“…This will require carefully planned randomized trials to investigate the benefits and safety in these other conditions. There are already promising results from animal models suggesting its potential use ischemic stroke [42] and in shock (post-resuscitation). [43] Therapeutic hypothermia has also been employed in the management of pediatric conditions such as hypoxic ischemic encephalopathy, [44] birth asphyxia, [45] and pediatric cardiac arrest, which in children and infants, results mostly from asphyxia rather than VF, which is the major cause in adult patients.…”
Section: Recommendations For Use Of Therapeutic Hypothermiamentioning
confidence: 97%